MALIGNANT PARAGANGLIOMA IN AN ADOLESCENT - Affendi, Sharifah Noor Adrilla binti Long Mohd Noor; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pheochromocytomas (PCC) and paragangliomas (PGL) (PPGL) are rare neuroendocrine tumours occurring in children and adolescents. Nevertheless, they are the most common endocrine tumours in the paediatric population and account for 0.5–1% of paediatric hypertensive cases. We describe a 16-year-old female with malignant paraganglioma. CASE A previously healthy 16-year-old female presented with a one-month history of intermittent headaches associated with palpitations and presyncopal attacks. The first blood pressure reading revealed that she was hypertensive, with a BP of 159/116. She had no chest pain, shortness of breath, diaphoresis, abdominal pain, or diarrhoea. There is no family history of hypertension in the young or endocrine disorder. The patient is lean with a BMI of 14.2 kg/m2 . No goitre, cushingoid or acromegalic features were present. The hormonal workup done was consistent with phaeochromocytoma (normetanephrine: 55.30 umol/ day) (35.5 X ULN) ). Other forms of work-up for secondary hypertension were unremarkable. Adrenal CT imaging revealed an enhancing mass at the left pararenal space measuring 4.1 x 4.7 x 4.7 cm with local infiltration to the tail and body of the pancreas complicated by a left renal infarct. Therefore, she was diagnosed with left paraganglioma with local infiltration. Preoperatively, she was started on oral prazosin 1 mg, 6 hourly and oral bisoprolol 2.5 mg daily and successfully underwent open resection of the left paraganglioma. Unfortunately, she remained hypertensive post-surgery, indicating a possible malignant paraganglioma. Thus, she was restarted on antihypertensive medications. Gallium-DOTATE scan and genetic testing have been arranged to aid further management. CONCLUSION Diagnosis of pheochromocytoma and paraganglioma is paramount during the evaluation of secondary hypertension in the paediatric population. Although they are uncommon, possible curative surgery can be offered. All children should be subjected to genetic testing given the high rate of inheritance of these tumours. Subsequently, all patients with genetic mutations ought to be under lifelong surveillance in view of the risk of recurrence and malignancy.